Nanofiltration membrane processes for water recycling, reuse and product recovery within various industries: A review. (February 2022) - Ahmad, Nor Naimah Rosyadah; Ang, Wei Lun; Teow, Yeit Haan; Mohammad, Abdul Wahab; Hilal, Nidal
Abstract: Nanofiltration (NF) membrane has been applied for the treatment of wastewater owing to its unique features such as higher selectivity towards divalent/polyvalent ions while allowing permeation for monovalent ions and small molecules of less than 100 Da. Thus, the use of NF in wastewater treatment is promising for water recycling, reuse, and recovery of other valuable products in industrial wastewater treatment. This review highlights the current application of NF for water recycling, reuse, and product recovery within multiple industries such as textile, food, oil and gas, mining, tannery, pharmaceutical as well as pulp and paper industry. The performance of NF either as stand-alone or integrated with other processes for improving the overall treatment efficiency and minimizing membrane issues is discussed. Finally, future perspectives for NF applications in industrial wastewater treatment for water recycling, reuse, and product recovery are discussed. Highlights: Water recycling and reuse is becoming very important for sustainable development. Membrane technology can play very important role in water recycling and reuse. Apart from water recovery, valuable products can also be recovered. Nanofiltration (NF) membrane is unique and provide opportunities for reuse and recovery. Integrated technologies with NF membrane can improve efficiency and higher performance.